2001
DOI: 10.1002/jbm.10025
|View full text |Cite
|
Sign up to set email alerts
|

Serological analysis of patients treated with a new surgical hemostat containing bovine proteins and autologous plasma

Abstract: A randomized, controlled clinical study of the management of diffuse bleeding with CoStasis surgical hemostat, a new hemostat containing bovine thrombin and collagen with the patient's own plasma, included patients undergoing cardiac, hepatic, iliac, and general surgery. Sera from 92 patients treated with CoStasis and 84 control patients were collected preoperatively and at a post surgical follow-up of 8 weeks. Among the control group, 57 patients were treated with Instat collagen sponge in noncardiac indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 44 publications
(62 reference statements)
1
39
1
Order By: Relevance
“…In 167 general, hepatic, cardiac, and orthopedic patients, CoStasis (Cohesion Technologies, Inc., Palo Alto, CA), a new formulation of thrombin and collagen composite, was compared with 151 similar surgical patients who received a control hemostat for hemistatic success and safety. Investigators found that CoStasis patients were more likely to demonstrate bovine thrombin antibodies than control hemostat exposed patients (48% positive or equivocal versus 19% P 0.01) [43,45]. Despite the fact that more than 80% of these patients had been exposed to thrombin in previous surgeries, only two ''nonserious adverse events occurred in one patient [which was] attributed to the use of Costasis'' [43,45].…”
Section: Rctsmentioning
confidence: 95%
See 3 more Smart Citations
“…In 167 general, hepatic, cardiac, and orthopedic patients, CoStasis (Cohesion Technologies, Inc., Palo Alto, CA), a new formulation of thrombin and collagen composite, was compared with 151 similar surgical patients who received a control hemostat for hemistatic success and safety. Investigators found that CoStasis patients were more likely to demonstrate bovine thrombin antibodies than control hemostat exposed patients (48% positive or equivocal versus 19% P 0.01) [43,45]. Despite the fact that more than 80% of these patients had been exposed to thrombin in previous surgeries, only two ''nonserious adverse events occurred in one patient [which was] attributed to the use of Costasis'' [43,45].…”
Section: Rctsmentioning
confidence: 95%
“…Both edema and mild foreign body reaction ''resolved without incident'' [43,45]. The investigators observed that ''no adverse events or bleeding complications'' occurred in patients with high titers and that overall, ''no serious adverse events [were] related to the use of CoStasis'' [43,45].…”
Section: Rctsmentioning
confidence: 98%
See 2 more Smart Citations
“…5 Although topical bovine thrombin preparations have been used successfully in most patients with isolated reports of serious adverse events, deranged hemostasis has developed in some surgical patients, resulting in severe or refractory bleeding and/or thrombosis. 8 It is thought that impurities in bovine thrombin preparations might be responsible for the adverse reactions. Patients exposed to topical thrombin preparations may develop antibodies to bovine thrombin, factor V/Va, and various other proteins found in these preparations.…”
mentioning
confidence: 99%